Brain Tumor: An overview of the basic clinical manifestations and treatment - Abolanle AA Kayode; Amina Shahzadi; Muhammad Akram; Hina Anwar; Omowumi T Kayode; Omowumi O Akinnawo; Sunday O Okoh (Global Journal of Cancer Therapy - Peertechz Publications, 2020)
We review the basic clinical manifestation, diagnosis and management of brain tumor.  Google search was done by using different terms associated with brain tumor and different databases were used, such as Google Scholar, Cochrane Database, and Science Direct etc.  In spite of the fact that clinical manifestations fluctuate on the basis of category, magnitude and site of tumor, the most common clinical features reported are persistent headache, seizures, nausea and vomiting, loss of consciousness, dizziness, mood fluctuation, cognitive problems, visual defects, weakness of body parts, difficulty with speech and language, and hearing impairment. Apart from neurologic examination, diagnostic approaches include Computed Tomography (CT) scan, MRI and biopsy.  Treatment strategies, determined by a variety of factors, include surgery, radiotherapy, chemotherapy and indicative therapy. This mini-review summarizes brain tumor biology as regards its classification, grading, risk factors, clinical presentation, diagnostic tools and treatment modalities.